The view from Coral Cove [large type] - Clipston, Amy (Thorndike Press large print Christian romance series., 2022)
"When a jilted romance novelist escapes to a small beach town, the last thing she expected to find was the start of an even better love story. In the wake of a broken engagement and the death of her last surviving family member, sweet romance novelist Maya Reynolds moves to the haven of Coral Cove, North Carolina, to take over her great-aunt's toy store. Some of her grief is immediately eased by imaginative eight-year-old Ashlyn Tanner, who talks her into adopting a kitten and inspires Maya to create a princess tea-party room in the store. Ashlyn's dad, local veterinarian Brody Tanner, is quickly smitten by the newest resident of his hometown. As a single parent, he sacrifices a lot in order to give Ashlyn the world, so a romantic entanglement with Maya is not a distraction he is looking for. As the three develop a deepening bond in the seaside town where Maya experienced some of her happiest childhood memories, clouds cast a shadow over Maya's hope for the future: an impossible deadline looms over her next novel, a long-held secret by her late mother about Maya's absent father comes to light, and Brody's resolve to avoid romance seems unbreakable. But together, they just might discover that sometimes happy endings happen outside the pages of Maya's novels too"--